Pemanfaatan TikTok sebagai Media Promosi Digital Difabelzone - Giza Pudrianisa, Sheila Lestari; Damastuti, Riski; Yudhistira, Nurfian; Wijaya, Jeni Novianti; Fajriyah, Nur; Ariamanda, Revasya Arnes; Fitriani, Aulia Freza (Universitas Pahlawan Tuanku Tambusai, 2025)
Social media is an important strategy for promotional activities, one of which is TikTok. Where this platform is a tool to introduce products by influencing and convincing buyers visually and audiovisually. Without strong promotion through digital, the products marketed are less able to compete. As a result, sales do not increase. Seeing this problem, many people do not understand the benefits of TikTok as a promotional tool amidst the onslaught of technology. One of them is the Difabelzone community. So, the purpose of this community service is to provide understanding and training related to optimizing TikTok as a promotional media to improve the skills of people with disabilities in utilizing digital media. The approaches used include observation, socialization/training, and evaluation. This method is used so that community members can compete with various competitors, products are increasingly in demand without being limited by distance and time and sales volumes are increasing. The community can easily take advantage of developing digital technology, so that inclusivity occurs in people's lives. The increase in understanding and skills of Difabelzone using TikTok in the form of creating simple content, utilizing various features and filters, TikTok Shop, hashtags and interesting captions have a positive impact slowly and surely in expanding market share through digital promotion.